2004
DOI: 10.1080/10408690490424649
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Quality and Postharvest Properties of Vegetables: Integration of Water Relations and Metabolism

Abstract: Growing of vegetables in the field, harvesting, handling in the packing house and storage are events in the lifetime of vegetables that are analysed from the point of view of the complex series of physiological transitions taking place in each of these events. Water is the major factor limiting plant metabolism and plants have developed fascinating mechanisms to cope with this limiting factor. Therefore, water relations (water, pressure and osmotic potential) are used as criteria for discussing plant stress ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 95 publications
0
26
0
2
Order By: Relevance
“…The differences in dry matter content, which may be due differences in fructan concentration, could result in an increase in cell water potential and cell turgor, which may lead to firmer plant tissue and increased postharvest lift. 13,32,33,34 In addition, nearly 90% of weight loss in onion bulbs during storage has been attributed to water loss. 35 Thus it may be possible that changes in firmness could be due to water loss and changes in turgor.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in dry matter content, which may be due differences in fructan concentration, could result in an increase in cell water potential and cell turgor, which may lead to firmer plant tissue and increased postharvest lift. 13,32,33,34 In addition, nearly 90% of weight loss in onion bulbs during storage has been attributed to water loss. 35 Thus it may be possible that changes in firmness could be due to water loss and changes in turgor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that membrane lipids of chilling‐sensitive plants undergo phase transition from a liquid crystalline state to a solid gel phase at the critical temperature at which CI occurs. The formation of gel phase lipid is followed by a series of degradative processes leading to the loss of cellular compartmentation 10. Previous studies have shown that the degradation of membrane lipids is achieved by the concerted activities of a variety of phospholipases, including phospholipase D (PLD, EC 3.1.4.4) and phospholipase C (PLC, EC 3.1.4.3) 11.…”
Section: Introductionmentioning
confidence: 99%
“…This water deficit during storage mainly affects the turgidity of fruit tissues, affecting the loss of this will affect several metabolic functions, but above all, changes in texture, leading to a loss of fresh product and affects the quality of its [35].…”
Section: Variation Of Moisture Content and Weight Loss During Storagementioning
confidence: 99%